Rola Republiki Federalnej Niemiec w wizji polskiej prezydencji w Radzie Unii Europejskiej - BIELAWSKA, AGNIESZKA (Rocznik Integracji Europejskiej, 2012)
This paper is an attempt to answer the question of the role R. Sikorski attributed to Germany during the Polish Presidency. Its aim is to examine the main proposals of the Minister of Foreign Affairs to combat the deepening debt and crisis of confidence in terms of their compliance with the proposals of the representatives of the German government. It is also an attempt to answer the question of whether, and if so how, the Minister’s speech affected Polish-German relations.